Kajian Ilmu Kalam di IAIN Menyongsong Perguliran Paradigma Keilmuan keislaman pada Era Milenium Ketiga. - Muhammad Amin Abdullah (Al-Jami'ah: Journal of Islamic Studies, 2000)
The paper is aiming at offering new paradigm in studying Islamic theology. It starts by describing the existing theological discourse in Indonesian Islamic higher education. It is found that theology, due to its important and central position in religion, has been sacralized. The historical aspect uf its logic, methodology and development are being protected from criticism cannot be evaluated and reformulated. As a result most Muslims find it difficult to establish a mutual dialog with people of other religions in this pluralistic world and on the social, economic, cultural and political spheres.  Before proposing a new approach in studying theology, the paper forwards epistemological-methodological questions: Is it possible to combine or establish a dialog between philosophy and theology? Is it allowed to review and reformulate all systematic structure, content and methodology in theology developed by classical and medieval theologians to meet the new needs and changes? Can it be said that what is now called theological doctrine or dogma is nothing other than theory developed by human beings living in a particular time and space? The answers of these questions will determine the nature of the study of theology in the future.